Scientometric insights into urban sustainability: exploring the vulnerability-adaptation-settlements nexus for climate resilience - Jiang, Jingjun; Cai, Daran; Yang, Qi; Huang, Malan (Frontiers in Environmental Science, 2025)
As global urbanization accelerates, the rapidly growing urban population poses significant challenges to the realization of sustainable development. The Urban Vulnerability–Adaptation–Settlements (VAS) nexus has emerged as a critical research domain to address these challenges. This study conducts a bibliometric analysis of 887 highly cited publications from the Web of Science Core Collection to identify key scholars, research institutions, countries, core research domains, and emerging trends in the field. The findings reveal that: (1) Research related to the Urban VAS nexus can be divided into three developmental phases: the initial budding stage (1958–1991), the high-growth stage (1992–2018), and the stable development stage (2019–2024); (2) Current research primarily focuses on population urbanization, land urbanization, and industrial development, while addressing core issues such as environmental sustainability, social equity, smart governance, and community development; (3) Future research should place greater emphasis on the development of smart cities, green infrastructure, and energy transitions, while also exploring policy innovations and technological advancements to foster a more equitable and sustainable urban future. Based on the finding, this study argues that the key to future urban development lies not in the “speed of growth” but in the “quality of resilience.” Researchers are encouraged to promote multi-scale, multi-dimensional studies of VAS coupling mechanisms, while integrating smart governance, green transitions, and inclusive development goals into urban policy and practice.